Nommer et décrire les soieries façonnées. Apports et limites d’une comptabilité princière - Nadège Gauffre Fayolle (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
To Study Textiles, whatever the context, is above all to know how to identify, name and describe the materials. During the 20th Century, three major research centers developed technical vocabularies. However, many medieval textiles cannot be studied directly with these reading grids, which are too contemporary. It is therefore important to use medieval sources to re-examine the vocabulary and to refine technical definitions. The accounts of the Savoyards princes in the 14th and 15th Centuries, which record sumptuary expenses, are precious testimonies of lexicographical usage, the diffusion of the different silks and the tastes of the men and women of the society of the time.